Simple colon ulcer - Ugarte, Raúl; Suaya, Hadel (Cirugía del Uruguay, 2020)
A case of plain ulcer in the transverse colon is reported upon. .This localization is of very rare occurrence ( 2-3 % of findings). The diagnosis was based on clinical findings and preceded the pathologist's report. Pathogenesis, diagnosis and therapy are discussed in conjunction with the various forms of the ulcer and with clinical cour.se ( plain, callous, inflammatory tumor, perforating and hemorragic complications).